3D DLP PRINTER - Štekels, Kārlis; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Last dacade, the 3D printers got a lot of popularity. 3D printer is CNC machine, which can create a physical three-dimensional objects. Digital light processing stereolithography (DLP) 3D printers uses a UV laser to cure a polymer. It is carried out the advantages and disadvantages of a given type of 3D printing technology.